Aging and Health in Africa
XII, 244 p.
Keywords: Countries with a high percentage of elders risk a serious disease burden and increasing stress on health and social welfare systems.Nowhere is this more evident than on the African continent, where high poverty rates, civil unrest, and unsteady government structures exist alongside medical advances and longer lifespans. Aging and Health in Africa examines this multilayered scenario in abundant detail, providing both a continent-wide overview and nation-specific dispatches regarding an often-marginalized population. The book’s demographic and socioeconomic profile of elders clarifies the connection between aging and health, and offers keys to better understanding our aging planet. Current and emerging policies and programs to improve health promotion and health care for older people are critiqued, and the author analyzes what still needs to be done to achieve world health goals, especially as nations continue to modernize and rebuild. For each country, the relationship is explored between the experience of elders and the larger social context, including: South Africa: the situation of the “nearly old.” Uganda: the impact of HIV/AIDS on the elderly. Camaroon: elder care arrangements in rural areas. Ghana: elder health and health-seeking behaviors. Congo: health perspectives of older people. Rwanda: understanding the experiences of the rural elderly. A groundbreaking research reference for a wide range of readers including Africa specialists,cross-cultural psychologists, sociologists, demographers, gerontologists,public health professionals, policymakers, and advocates, Aging and Health in Africa will be valued by an engaged,interdisciplinary audience.